Alur Produksi Udang Vaname (Litopenaeus Vannamei) Beku di PT MMC Kabupaten Pulau Morotai - Titien Sofiati; Asy’ari Asy’ari; Isma Kastanya; Siti Nurbaya Deto (Jurnal Ilmiah Wahana Pendidikan, 2021)
Prawns is the main export commodity in Indonesia for decades. The prawn's product that the most standout of Indonesia’s export which is frozen prawns from PT. MMC at Regency of Morotai Island, the only company that produced frozen prawns of Vaname (Litopenaeus vannamei) in province of North Maluku. The purpose of this research is to explain the production cycle of frozen Vaname prawns in PT. MMC. This research is expected can give the information about frozen Vaname prawns, and as the basic data for further research. The result showed that production cycles of frozen Vaname prawns in PT. MMC consists of: harvest, cleaning I and cleaning II, soaking Melside, sizing, measuring and compiling, freezing, glazing, packing and labeling, and saving in cold storage. The market of frozen Vaname prawns PT. MMPT already reached on to national and international markets.